Three‐dimensional multi‐fluid simulations of Titan's interaction with Saturn's magnetosphere: Comparisons with Cassini's T55 flyby. Issue 8 (2nd August 2013) - Snowden, D.; Winglee, R.
Abstract : [1] We describe a new multi‐fluid model of Titan's interaction with Saturn's magnetosphere that includes finer resolution in Titan's ionosphere, photoionization, electron‐impact ionization, dissociative recombination, and ion‐neutral coupling in the momentum and energy equations. We compare simulation results to data from Cassini's T55 flyby to show that including magnetospheric electron‐impact ionization in Titan's nightside ionosphere is necessary to calculate electron densities, electron temperatures, and ion velocities that are consistent with Cassini observations. However, similar to other studies, we find that the electron‐impact ionization rate calculated by the model needs to be significantly reduced to produce an electron density that is in agreement with the observations. We also find that an upstream plasma flow with significant components northward and radially outward from Saturn is needed to reproduce the gradual increase in electron density observed during the ingress portion of T55. This suggests that Titan was in a nonideal environment with a plasma flow oriented away from the direction of corotation during T55 and likely during the subsequent flybys T56, T57, T58, and T59 when similar electron density enhancements were seen on the inbound portion of Cassini's trajectory. Key Points: Results of the model are consistent with data from Cassini's T55 flyby Auroral ionization is needed to simulate the observed electron density The upstream plasma flow may not have been co‐rotational during T55